Balancing Market Share Growth and Customer Profitability: Budget Allocation for Customer Acquisition and Retention - Tsao, Hsiu-Yuan; Matthews, Lucy M.; Crittenden, Victoria L. (Organizations and Markets in Emerging Economies, 2012)
This study adds to the knowledge of budget allocation for customer acquisition and retention spending in an inertia segment.  The results indicate that when retention spending surpassed the optimal budget allocation, increased spending did not grow the expected value of customer equity.  Since the inertia segment is comprised of loyal customers, an examination of brand equity and its role in customer loyalty and its influence on customer equity are discussed.
Keywords: customer equity; brand equity; theory of reasoned actions; retention spending